2017
DOI: 10.1002/path.4978
|View full text |Cite
|
Sign up to set email alerts
|

Genomic profiles of lung cancer associated with idiopathic pulmonary fibrosis

Abstract: Little is known about the pathogenesis or molecular profiles of idiopathic pulmonary fibrosis-associated lung cancer (IPF-LC). This study was performed to investigate the genomic profiles of IPF-LC and to explore the possibility of defining potential therapeutic targets in IPF-LC. We assessed genomic profiles of IPF-LC by using targeted exome sequencing (OncoPanel version 2) in 35 matched tumour/normal pairs surgically resected between 2004 and 2014. Germline and somatic variant calling was performed with GATK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 71 publications
0
34
0
Order By: Relevance
“…The corresponding positive predicting value was 64% and, therefore, the false discovery rate was 36%. In order to compare our algorithm with other CNV detection softwares, the same validation cohort was analyzed with CONTRA v.2.0.8 [20] and CNVKIT v.0.8.6 [21], for which effectiveness and reliability have been previously widely proved [22]. The best results were those achieved with our algorithm and CNVKIT, both in terms of accuracy (99.9%, whereas for CONTRA it was 99.6%) and sensitivity (100%, whereas for CONTRA it was 87.3%).…”
Section: Algorithm Validationmentioning
confidence: 99%
“…The corresponding positive predicting value was 64% and, therefore, the false discovery rate was 36%. In order to compare our algorithm with other CNV detection softwares, the same validation cohort was analyzed with CONTRA v.2.0.8 [20] and CNVKIT v.0.8.6 [21], for which effectiveness and reliability have been previously widely proved [22]. The best results were those achieved with our algorithm and CNVKIT, both in terms of accuracy (99.9%, whereas for CONTRA it was 99.6%) and sensitivity (100%, whereas for CONTRA it was 87.3%).…”
Section: Algorithm Validationmentioning
confidence: 99%
“…In our cohort, >80% of SCC cases with IPF also harbored activating p53 mutations, as assessed by immunohistochemistry, implying that these mutations are crucial to the development of carcinomas with IPF, although there was no significant difference in incidence of p53 mutations compared to SCC without IPF. Recently, Hwang et al 10 found that lung cancer with IPF showed frequent BRAF mutations (17.1%) APOBEC3-related mutational signatures. Of note, APOBEC3 is known to be induced by exogenous factors such as viral infection, while Folcik et al 48 reported that lungs with IPF are frequently infected by herpesvirus saimiri.…”
Section: Discussionmentioning
confidence: 99%
“…IPF is a persistent and chronic inflammatory disease that can be triggered by complex interactions between genetic and environmental factors such as cigarette use, although cancer development in fibrotic lungs occurs independently of cigarette smoking . Recently, exome sequencing revealed APOBEC‐related mutagenesis in lung cancers with IPF, suggesting viral and/or immune‐related mutagenic processes . Squamous cell metaplasia was also reported to frequently occur in peripheral honeycombed tissues of cancerous lungs with IPF .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…vi) CDKN2A, p16 INK4a : Cellular senescence markers, including p16 INK4a , induce interstitial remodeling, ECM deposit and pulmonary fibrosis (42). vii) BRAF: BRAF has been shown to be overexpressed and mutated in IPF samples (43). The high incidence of BRAF mutations has been observed in pulmonary fibrosis, most notably the BRAF V600E mutation profile (43).…”
Section: The Driver Genes In Endometriosis As a Major Hallmark Of Fibmentioning
confidence: 99%